Efficacy of the Nav1.7 blocker PF-05089771 in a randomised, placebo-controlled, double-blind clinical study in subjects with painful diabetic peripheral neuropathy - McDonnell, Aoibhinn; Collins, Susie; Ali, Zahid; Iavarone, Laura; Surujbally, Raulin; Kirby, Simon; Butt, Richard P (Pain (Amsterdam), 2018)
The effect of PF-05089771, a selective, peripherally restricted Nav1.7 sodium channel blocker on pain due to diabetic peripheral neuropathy was investigated in a randomised, placebo and active-controlled parallel group clinical trial (NCT02215252). A 1-week placebo-run in the period was followed by a 4-week treatment period and a 1-week placebo run-out/taper-down period. Single-blind placebo was administered throughout run-in and run-out periods. Subjects were randomised to receive either PF-05089771 150 mg twice daily, pregabalin 150 mg twice daily, or placebo during the 4-week treatment period. One hundred thirty-five subjects were randomised. The primary endpoint was the average pain score derived from subjects' Numerical Rating Scale scores over the past 7 days of week 4 of the double-blind treatment period. Predefined efficacy criteria for the trial were the effect of PF-05089771 being >0.5 units better than placebo at interim analysis after completion of the first part of the study. Although a trend for a reduction in the weekly average pain score in the PF-05089771 treatment group was observed, this was not statistically significant when compared with placebo at week 4, with a mean posterior difference of -0.41 (90% credible interval: -1.00 to 0.17). The effect of PF-05089771 was smaller than that seen with pregabalin, which was statistically significant when compared with placebo at week 4, with a mean posterior difference of -0.53 (90% credible interval: -0.91 to -0.20). As predefined efficacy criteria were not met, the study did not proceed to the second part. PF-05089771 was well tolerated. Possible reasons for the modest efficacy observed with PF-05089771 are discussed.